Violence suffered by nursing professionals in the emergency service (Research, Society and Development, 2022)
Objective: To identify the types of violence suffered by nursing staff and determine the feelings of professionals facing cases of violence suffered. Method: Exploratory, descriptive study with a qualitative approach, having as subjects the nursing professionals with more than one year in the unit. Results: Thirty professionals were interviewed, being 9 (30%) nursing technicians and 4 (13.33%) nurses. The sample was composed entirely by female 30 (100%). The prevalent age group was 31 and 40 years old. Of the interviewees, 27 (90%) claimed to have suffered verbal violence and, 10 (33.33%) suffered psychological violence. Regarding the feelings that the professionals felt when faced with the violence suffered, 7 (23.33%) reported feeling powerless and 7 (23.33%) said they felt hatred. Conclusion: It was possible to raise the profile of violence suffered by professionals, which were verbal, psychological and harassment. It was observed that the nursing professionals refer a feeling of powerlessness and sadness in front of the violence they suffer in the units where they work. According to the results, it is clear that violence can bring serious problems to the personal and professional lives of these workers.